Keefektifan Bimbingan Kelompok Teknik Modelling Simbolik bagi Peningkatan Perencanaan Karier Siswa SMP - Christina Ifanta Pratiwi; Awalya; Muslikah (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
This study aimed to determine the effectiveness of group guidance services using symbolic modelling techniques in improving career planning among ninth-grade students at SMPN 1 Karangsembung. The novelty of this study lies in the application of symbolic modelling techniques in group guidance services to enhance students’ understanding of self-potential, career information, and career decision-making. The study employed a quantitative approach with a pre-experimental method and a one-group pretest-posttest design involving 10 students selected through purposive sampling. Data were collected using career planning scales, observations, and interviews. The results showed that students’ career planning increased from 51% in the low category to 73% in the high category after the treatment. The Paired Sample T-Test showed a significance value of 0.000 < 0.05, indicating that symbolic modelling techniques were effective in improving students’ career planning.